2023
DOI: 10.1155/2023/2334675
|View full text |Cite|
|
Sign up to set email alerts
|

5-Fluorouracil-Loaded PLGA Nanoparticles: Formulation, Physicochemical Characterisation, and In VitroAnti-Cancer Activity

Abstract: The major goal of this investigation was to prepare a drug delivery of polymeric nanoparticles (NPs) from 5-fluorouracil (FU) that could be delivered intravenously and improve the therapeutic index of the FU. In order to achieve this, interfacial deposition method was used to prepare FU entrapped poly-(lactic-co-glycolic acid) nanoparticles (FU-PLGA-NPs). The influence of various experimental settings on the effectiveness of FU integration into the NPs was assessed. Our findings show that the technique used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…When cells were treated with a 5-FU solution, cell viability decreased by 70%, whereas 5-FU-PLGA-NPs containing the same drug dose induced nearly 100% cell toxicity. This suggested that the delivery system may significantly enhance intracellular drug accumulation and improve therapeutic efficacy (Gahtani et al, 2023).…”
Section: Poly (Lactic-co-glycolic Acid) (Plga)mentioning
confidence: 99%
“…When cells were treated with a 5-FU solution, cell viability decreased by 70%, whereas 5-FU-PLGA-NPs containing the same drug dose induced nearly 100% cell toxicity. This suggested that the delivery system may significantly enhance intracellular drug accumulation and improve therapeutic efficacy (Gahtani et al, 2023).…”
Section: Poly (Lactic-co-glycolic Acid) (Plga)mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%